Theories of international relations - Burchill, Scott 1961-; Linklater, Andrew; Devetak, Richard; Donnelly, Jack; Nardin, Terry; Paterson, Matthew; Reus-Smit, Christian; True, Jacqui (Palgrave Macmillan, 2009)
The fully updated and revised fourth edition of this widely-used text provides a comprehensive survey of leading perspectives in the field including entirely new chapters on Historical Sociology by Andrew Linklater and International Political Theory by Terry Nardin